Impact of intellectual human capital and ICT on bank efficiency in Malaysia / Dr. Rosita Suhaimi ... [et al.] - Suhaimi, Rosita; Ibrahim, Nurhani Aba; Chong, Fen Nee; Voon, Boo Ho (UITM Sarawak,Kampus Samarahan, 2012)
This paper attempts to identify the significance of Information and Communications Technology (ICT) and intellectual human capital to the profit efficiency of commercial banks in Malaysia. The profit efficiency of commercial banks in Malaysia was estimated using the Stochastic Frontier Approach (SFA) on a sample of unbalanced panel data, covering 23 commercial banks, between 1995 to 2009. Based on the empirical results, both ICT and non ICT stock expenditure were found to exert significant positive impact on profit inefficiency, whereas intellectual human capital, size and ownership were negatively significant contributors.